The Pathway Toward Clinical Self Confidence - Bischoff, Richard J.; Barton, Marci (The American journal of family therapy, 2002)
This study was designed to determine the most common pathway toward the development of clinical self-confidence for therapists during the first year of client contact. Telephone interviews were conducted with 39 recent graduates of a master's level marriage and family therapy program. Subjects were asked to graph their development of clinical self-confidence over the first 12 months of their clinical experience. Results reveal a three-stage model of therapist development. The implications for training within each stage of development are identified with an emphasis on the role of the supervisor.